The Relationship between Positive Thinking and Academic Achievement among Students of Education College at Princess Nourah University at the Saudi Kingdom - Alwail, Amal Omar (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the relationship between positive thinking and academic achievement among students of the College of Education, on a sample of (201) female students from the College of Education at Princess Noura University for the academic year 2018-2019. The instrument of the study was the positive thinking scale prepared by Abdul Sattar Ibrahim (2008). The researcher used the descriptive- analytical approach to achieve the research objectives, due to its methodological and procedural relevance to the nature of the variables of this research. The statistical methods represented in the arithmetic means, standard deviations, frequencies, percentages, Pearson correlation coefficient, and (T) test for differences between groups. The study reached a number of results, the most prominent of which were: The study sample had a high degree of positive thinking, with an arithmetic average (77.16), and the results indicated that there were no statistically significant differences between students in the psychology and kindergarten departments due to the thinking pattern (positive-negative), as well as the results indicated that there were no statistically significant differences between high-achieving students and low-achieving students in the average degrees of the positive thinking scale dimensions or in the medium total degree of the scale.
Keywords: Positive Thinking; Academic Achievement; Students; Princess Nourah University; Saudi Kingdom; Thinking Patterns; University Female students; School Consensus; Negative Thinking; Academic Excellence